The Prion Basis of Progressive Neurodegenerative Disorders - Joshi, Tvisha; Ahuja, Nidhi (Interdisciplinary Perspectives on Infectious Diseases, 2023)
The discovery of proteinaceous infectious agents by Prusiner in 1982 was sensational. All previously known pathogens contained nucleic acids, the code of life, that enabled them to reproduce. In contrast, the proteinaceous agents of disease, called prion proteins (PrP), lacked nucleic acids and propagated by binding to the functional, endogenous form of cellular prion protein (referred to as PrPC) and altering its conformation to produce the infectious disease-causing misfolded protein (referred to as PrPSc). The accumulation and aggregation of these infectious prion proteins within the brain cause destruction of neural tissue and lead to fatal spongiform encephalopathies. In this review, we present the molecular pathology of prion-based diseases. These insights are of particular importance since the principles of prion pathogenesis apply to other neurodegenerative diseases such as Alzheimer’s disease, Huntington’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis. Collectively, the global prevalence of these diseases is rapidly increasing while effective therapies against them are still lacking. Thus, the need to understand their etiology and pathogenesis is urgent, and it holds profound implications for societal health.